Caspase-11/4 is involved in bacteria-mediated periodontitis by promoting the release of interleukin-1 β and tumor necrosis factor-α. (October 2022) - Li, Zuntai; Cai, Qing; Li, Birong; Meng, Weiyan
Abstract: Objective: This study investigated the main mechanism and role of caspase-11/4 as a pattern recognition receptor (PRR) in periodontitis through caspase-11 inhibition. Design: Clinical tissue samples were collected from patients with periodontitis and healthy volunteers and evaluated through hematoxylin–eosin (HE) staining, immunohistochemical (IHC) staining, and real-time quantitative PCR (RT-qPCR). In the rat periodontitis model, both these staining procedures, RT-qPCR, and western blotting were used to evaluate the histological, mRNA, and protein levels of caspase-11, interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α). In vitro, the role of caspase-11, inhibited by siRNA, was investigated by analyzing the mRNA and protein levels of IL-1β and TNF-α in Porphylinomonas gingivalis (P. gingivalis) lipopolysaccharide (LPS)-stimulated Raw264.7 macrophages. Results: Histological and molecular biological results of clinical and experimental animal periodontitis samples indicated that caspase-11/4 mRNA and protein levels significantly increased in inflammatory tissues. Caspase-11 is mainly distributed in leukocytes, which are labeled by CD45 in the submucosa. In vitro results further confirmed that the expression of caspase-11/4, IL-1β, and TNF-α significantly increased in LPS-stimulated macrophages, and these changes were significantly attenuated by inhibiting caspase-11/4 expression. Conclusions: The function of caspase-11 in rat periodontitis models is similar to that of caspase-4 in human clinical periodontitis. IL-1β and TNF-α release in periodontitis depends on the recognition of P. gingivalis LPS by caspase-11/4. Highlights: IL-1β and TNF-α release in periodontitis depends on activation of caspase-11. The role of caspase-4 in homo periodontitis is similar to caspase-11 in rats. Caspase-11/4 maybe a key therapeutic target for periodontitis.